Analysis of Green Self Identity and Environment Concern on Adopt Electric Vehicle Intention with Perception of EV and Subjective Norm as Mediation Variables - Sugeng Purwanto; Hesty Prima Rini (International Journal of Social Service and Research, 2022)
The issue of environmental damage often arises in recent years, as a result of continuous and uncontrolled emission of harmful atmospheric pollutants. through various human activities. The consumption of fossil fuels by industry as well as the transportation system is considered to be the main reason, from which several studies have paid considerable attention to the pollution caused by vehicles. As indicated by the statistics of the International Energy Agency (IEA), a recent estimate of the number of one million vehicles used worldwide, with daily consumption of about 60 million barrels per day (nearly 70% of total oil production); nearly 36 million barrels of daily oil consumption is attributed to private vehicles, which cause the emission of 14 million tons of carbon dioxide. As a result, the replacement of conventional vehicles with renewable energy vehicles can be considered as a promising solution. In this regard, electric vehicles are expected to reduce negative effects on the environment and also help conserve scarce non-renewable fuel reserves throughout the life cycle. Electric Vehicles are considered an effective alternative to sustaining transportation through the reduction of oil dependence and subsequent air pollution, leading to significant health and environmental benefits. The purpose of this study is to analyze consumer behavior towards the intention to adopt an electric vehicle by involving the variables of Green Self Identity, Environment Concern, Perception of Electric Vehicle, and Subjective Norms. With 250 respondents spread across Indonesia and using the SmartPLS software, the results of a partial analysis of Green Self Identity proved to have an effect on Environment Concern. Meanwhile, Environment Concern was proven to affect Perception of EV and Subjective Norms, but did not affect Adoption Intention. For the indirect effect analysis, Perception of EV and Subjective Norms variables proved to be mediating variables between Environment Concern and Adoption Intention.